Critical Engaged Pedagogy to Confront Racism and Colonialism in (Geo) Science Education Through a Historical Lens - Emily J. Diaz-Vallejo; Ken Keefover-Ring; Elizabeth Hennessy; Erika Marín-Spiotta (Earth Science, Systems and Society)
The geosciences continue to grapple with the exclusion of Black, Indigenous, Latinx, and other students of Color. These patterns can be understood in the discipline’s roots in colonialism and extractivism. Furthermore, training of the scientific process as objective and race-neutral results in scientists who do not recognize how science can perpetuate inequities in society. Using a U.S. university biogeography course as a case study, we describe an innovative framework for teaching equity through a critical historical lens that interrogates: 1) biases in the processes and forms of knowledge production, legitimization, and exclusion; 2) the source of inequities in representation in the discipline; and 3) how societal benefits and harms of scientific practices are felt disproportionately demographically and geographically. Students were encouraged to critically analyze the historical context of scientific theories and their proponents and challenge assumptions about the representativeness of data supporting those theories into the present day. Engaging with these questions broadened students’ understanding of changing paradigms in the field and of links between colonialism and modern science. We provide recommendations for instructors seeking to use similar approaches to enhance student learning.